Eye injuries in open – clinic practice of Department of Ophthalmology Medical University Gdansk in 1992-1993 and 2002-2003 years - Homziuk, Magdalena; Łuksza, Lucyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of this study was the statistical and epidemiological analysis of patients with eye injuries. We analyzed all patients attending the emergency department of Department of Ophthalmology Medical University in Gdansk over the period of 1992-1993 and 2002-2003 years. We determined the visual function (isual acuity- distance and near Snellen acuity test, intraocular pressure measurement, biomicroscopy, ophthalmoscopy, X- ray examination and US -examination) in two groups of subjects. The 6427 patients were subjected in the first period (37% with eye injuries). In the second period we examined 10512 patients (44% with eye injuries). A total of visits have been examined in the firs period: 24.1% of patients were between 19-25 and 48% between 26-50 years. In the second group of patients 35.7% of patients were between 19-25 and 30.3% were between 26-50 years. In the both periods we observed mainly corneal injuries. Corneal foreign body and corneal abrasion were the most common etiology among close eye injuries in both groups. A total of visits have been examined: 7.78% with the first group and 8.95% was with burns. There were 1.89% in the first and 5.75% in the second period of severe eye injury such as penetrating ocular trauma, orbital fracture and intraocular foreign body. The main causative activity of ocular injuries in both groups was work (5.80% group I and 23.80% group II), assault (36.20% group I and 47.75% group II) and traffic accidents (4.84% group I and 12.05% group II). Results of our work indicated that ocular trauma is a common cause of improvement of visual acuity and a common cause of visit to the Emergency Department of Department of Ophthalmology.